Determinants of profitability: A case study of listed manufacturing companies in Sri Lanka - Nishanthini, A.; Nimalathasan, B. (My University, 2013)
The main objective of the study is to determine the profitability of listed manufacturing companies in Sri Lanka. In order to meet the objectives of the study, data were collected from secondary sources mainly from financial report of the selected companies, which were published by Colombo stock exchange in Sri Lanka. The results revealed that the profitability of manufacturing companies is less satisfactory. On the basis of result and analysis, selected manufacturing companies has different ranking based on each profitability indicators such as Gross Profit Ratio (GPR), Operating Profit Ratio (OPR), Net Profit Ratio (NPR), Return on Investment (ROI), and Return on Capital Employed (ROCE). Based on the Gross Profit Ratio, Operating Profit Ratio, Net Profit Ratio, ROYAL CHERAMIC PLC is at first whereas CHEVRON LUBRICANTS PLC is at first based on ROI, ROCE. Outcome of the study is beneficial to academicians, policy makers, practitioners and so on.
Keywords: Determination; Profitability; Manufacturing Companies